Prospective Investigation of Nasal Mupirocin, Hexachlorophene Body Wash, and Systemic Antibiotics for Prevention of Recurrent Community-Associated Methicillin-Resistant Staphylococcus aureus Infections - Miller, Loren G. (American Society for Microbiology, 2012)
Recurrent community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) skin infections are an increasingly common problem. However, there are no data on the efficacy of decolonization regimens. We prospectively evaluated 31 patients with recurrent CA-MRSA skin infections who received nasal mupirocin, topical hexachlorophene body wash, and an oral anti-MRSA antibiotic. The mean number of MRSA infections after the intervention decreased significantly from baseline (0.03 versus 0.84 infections/month, P = <0.0001). This regimen appears promising at preventing recurrent CA-MRSA infections.